Transformasi Birokrasi Pemerintahan Kota Kupang Berbasis Tata Kelola Kota Berkelanjutan - Pandie, David B.W.; Sjioen, Malisye Christin (Jurnal Inovasi Kebijakan, 2024)
The city of Kupang has historically developed over time, and is now transforming to create a sustainable city. The role of Kupang City as a multi-functional city: such as a government city, trade city, education city, industrial city and tourism city has triggered high urbanization and produced a complexity of problems that threaten the survival of city residents. The problem is that the government and city development model is not yet compatible with the principles of sustainability. Thus, bureaucratic transformation is a solution in efforts to build a civilized and sustainable Kupang City through an urban governance model. Collaboration between the government and all stakeholders is a determining factor in the effectiveness of urban governance, including changing the culture of city residents from passive to active citizens with urban culture as an agent for civilized and sustainable city development.